2020
DOI: 10.1093/rheumatology/keaa157
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hydroxychloroquine retinopathy in systemic lupus erythematosus: a case–control study with hydroxychloroquine blood-level analysis

Abstract: Objective HCQ is an essential medication in SLE, proven to lengthen survival and reduce flares. Its use, however, is limited by its rare but severe ophthalmological complications. Here, we aimed to analyse factors associated with HCQ retinopathy including HCQ blood levels. Methods This case–control study compared SLE patients with and without HCQ retinopathy, defined by abnormal results for at least two of the following ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 35 publications
3
18
1
Order By: Relevance
“…Also, we found that the cumulative dose of the hydroxychloroquine therapy was significantly related to the hydroxychloroquine retinopathy that was in agreement with Petri et al [ 23 ] and Lenfant et al [ 11 ]. Previously, the cumulative dose was described as one of the risk factors of the hydroxychloroquine retinopathy [ 14 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, we found that the cumulative dose of the hydroxychloroquine therapy was significantly related to the hydroxychloroquine retinopathy that was in agreement with Petri et al [ 23 ] and Lenfant et al [ 11 ]. Previously, the cumulative dose was described as one of the risk factors of the hydroxychloroquine retinopathy [ 14 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, weight-based daily dose was not a risk factor for HCQ retinopathy. However, the previous studies emphasized that the daily dose of more than 5 mg/kg is one of the most important risk factors for HCQ retinopathy [ 7 , 11 , 17 ]. The explanation might be that most of the studied patients’ weights were above 70 kg and most of them received 400 mg/day or less, also the low socioeconomic level of our patients might make them non-compliant to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with Dr. Yokogawa and colleagues that in the study by Lenfant et al (1), the lack of findings supporting a relationship between HCQ blood concentration and retinopathy may well have been due to the fact that Lenfant and colleagues selected an adherent control group, which likely inflated the average HCQ levels in their controls relative to typical patients.…”
supporting
confidence: 67%
“…HCQ blood levels were repeatedly measured prior to the onset of retinopathy in all patients. In contrast, the study by Lenfant et al was a case–control study, with cases and controls recruited from different sources, and in the controls, HCQ blood levels were measured only at a single time point (1).…”
mentioning
confidence: 99%
“…Petri et al report that higher blood levels of hydroxychloroquine (HCQ) predicted development of HCQ retinopathy (1). However, in a recent case-control study, HCQ blood levels were not associated with retinopathy (2). The inconsistency may arise from dosage adjustment over time and the timing of blood level testing.…”
Section: To the Editormentioning
confidence: 99%